Pa’bussuk Music as a Vehicle for Character Education: Educational Values and Learning Processes in Secondary Schools - Shophianto Tarampak; Rahma M; Syakhruni Syakhruni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The erosion of youth engagement with traditional arts and the poor integration of local wisdom into formal curricula challenge character education in Indonesian secondary schools. This study investigates the educational values embedded in Pa’bussuk, a Torajan bamboo percussion ensemble, and examines its pedagogical transmission mechanisms at Middle School 2 Balusu, North Toraja, Indonesia. Employing a qualitative descriptive design, data were generated through two cycles of participatory observation across eight structured practice sessions, semi-structured interviews with three key informants (teachers, instructors, and students), and documentation analysis. Data validity was ensured through source and methodological triangulation. Thematic analysis, guided by the Ministry of National Education’s character framework, identified four interconnected value clusters within Pa’bussuk organology and performance: root (integrity), culm (honesty), branch (cooperation), and leaf (creativity). Results indicated that across two instructional cycles, students demonstrated progressive internalization of five core character constructs, with communicativeness and responsibility showing the most robust development. The pedagogical pathway—comprising imitation, routine rehearsal, creative variation, and public performance—effectively bridged technical musical competence with affective character formation. This study concludes that Pa’bussuk practice constitutes a potent, multi-dimensional pedagogical medium. It provides a replicable, culturally responsive model for integrating traditional arts-based character education into formal secondary school curricula.